2018
DOI: 10.3390/md16080269
|View full text |Cite
|
Sign up to set email alerts
|

Marine Collagen/Apatite Composite Scaffolds Envisaging Hard Tissue Applications

Abstract: The high prevalence of bone defects has become a worldwide problem. Despite the significant amount of research on the subject, the available therapeutic solutions lack efficiency. Autografts, the most commonly used approaches to treat bone defects, have limitations such as donor site morbidity, pain and lack of donor site. Marine resources emerge as an attractive alternative to extract bioactive compounds for further use in bone tissue-engineering approaches. On one hand they can be isolated from by-products, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 41 publications
(47 reference statements)
2
45
0
Order By: Relevance
“…It was opioned that the morphalogical features of collagen such as fibril interconnectivity, shape and wall morphology were important factors in tissue engineering, since they may influence the growth, migration, proliferation, differentiation, and maturation of cells [ 26 ]. In recent research, the collagen from the same species (blue shark skin) was used to formulate a scaffold 3D matrix and tested the proliferation and mineralisation effect on Saos-2 cells, and further confirmed that the scaffold prepared from blue shark skin collagen could support Saos-2 cell attachment and osteoblast-like cells formation [ 14 ]. In the present study, the morphological features confirmed the aptness of blue shark skin collagens in bone tissue engineering.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…It was opioned that the morphalogical features of collagen such as fibril interconnectivity, shape and wall morphology were important factors in tissue engineering, since they may influence the growth, migration, proliferation, differentiation, and maturation of cells [ 26 ]. In recent research, the collagen from the same species (blue shark skin) was used to formulate a scaffold 3D matrix and tested the proliferation and mineralisation effect on Saos-2 cells, and further confirmed that the scaffold prepared from blue shark skin collagen could support Saos-2 cell attachment and osteoblast-like cells formation [ 14 ]. In the present study, the morphological features confirmed the aptness of blue shark skin collagens in bone tissue engineering.…”
Section: Resultsmentioning
confidence: 88%
“…Whereas dMC3T3TE1 cells showed similar cell proliferation in both ASC and PSC treated groups. A recent study by Diogo et al [ 14 ] reported that the composite blue shark skin collagen-calcium phosphate scaffold crosslinked with 12.5% EDC/NHS accelerated Saos-2 cells metabolic activity and supported osteoblast-like cells formation, however, this study was conducted using acid soluble collagen. Conversely, in the present study, the collagen was extracted by two different methods using acetic acid and pepsin, respectively, and the proliferative effect of freeze dried collagens was tested using dMBMS and dMC3T3E1 cells.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Marine organisms (sponges, jellyfish, molluscs and fish) are promising sources of collagen [14][15][16][17][18][19][20][21][22]. However, most of these marine-derived collagens are used in their hydrolyzed form, a step necessary for their efficient extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HMDI was also included as a cross-linker in the present study. Additionally, EDC and HMDI cross-linking were particularly suitable for dermal implants [30], for hard tissue application [31] or for bioprosthetic mesh materials [32].…”
Section: Introductionmentioning
confidence: 99%